A genetic algorithm application for automatic layout design of modular residential homes - De Almeida, A.; Taborda, B.; Santos, F.; Kwiecinski, K.; Eloy, S. (2016 IEEE International Conference on Systems, Man, and Cybernetics, SMC 2016, 2016)
This work presents an evolutionary approach that enables the automatic design of modular residential homes in mass customized production. Given a set of modular placement rules for the design, the formal problem can be viewed as a two-dimensional single large object placement problem with fixed dimensions and additional positioning constraints. This formulation results in the search of a floor plan layout constrained by dimensional and positional restrictions over a combinatorial size search space. A genetic algorithm strategy for the automation of floor plan design was implemented and shown to deliver the required design solution layouts. The layouts, when embedded into a proper graphical interface system will allow for future owners to acquire houses fitting their exact needs at affordable prices, improving the quality of living while simultaneously complying with a language of design.